2010
DOI: 10.1007/s00267-010-9436-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Groundwater Depth and Quality Parameters in the National Capital Territory of Delhi

Abstract: The groundwater quantity and quality scenario is of much concern in the National Capital Territory of Delhi, India, which necessitates an investigation to envisage the extent of spatial variability of groundwater depth and pollutant concentration levels in this region. Therefore, in this study, an effort was made to generate the spatial variability map of groundwater depth and quality parameters (viz. chloride, electrical conductivity, fluoride, magnesium, and nitrate). Ordinary kriging was used to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 23 publications
2
41
0
Order By: Relevance
“…Various studies also reported in 2011 that agricultural activities in the northern or central part of India resulted in a high concentration of nitrate or fluoride in groundwater, making it unsafe for drinking (25,26) . Moreover, a study in 2010 reported high nitrate concentration in groundwater in the study area of Delhi (27) and it was observed in the present study that more case mothers had migrated from rural areas of northern and central parts of India to Delhi. This is reflected in the fact that the women in our study who used more groundwater for drinking, which involved potential exposure to contaminants, had a higher risk of having children with NTD.…”
Section: Discussionmentioning
confidence: 89%
“…Various studies also reported in 2011 that agricultural activities in the northern or central part of India resulted in a high concentration of nitrate or fluoride in groundwater, making it unsafe for drinking (25,26) . Moreover, a study in 2010 reported high nitrate concentration in groundwater in the study area of Delhi (27) and it was observed in the present study that more case mothers had migrated from rural areas of northern and central parts of India to Delhi. This is reflected in the fact that the women in our study who used more groundwater for drinking, which involved potential exposure to contaminants, had a higher risk of having children with NTD.…”
Section: Discussionmentioning
confidence: 89%
“…These various groundwater aquifers (Figure 3) form hydrogeologic multi-layer entity where the relays are ensured by faults and vertical drainage [12]. Ben Baccar in 1982 has estimated the flow of the water pumped to 212 l/s and the minimum average flow sources to 5 l/s when the fictitious continued flow is 350 l/s.…”
Section: Dem and These Derivativesmentioning
confidence: 99%
“…Input to the batch subwatershed delineation function is a point feature class with point locations of interest [29]. The Batch Point Generation function can be used to interactively create such a file.…”
Section:  Subwatershed Delineationmentioning
confidence: 99%